The Role of the Board of Commissioners and Audit Committee in Influencing the Financial Performance of Banks Listed on the Indonesian Stock Exchange (IDX) - Sarah Febiola; Riri Mayliza; Lola Fitria Sari (Lembaga Riset dan Inovasi Al-Matani, 2023)
This research aims to determine the influence of the board of commissioners (DK) and audit committee (KA) on the financial performance of those listed on the Indonesia Stock Exchange in 2018-2022. The years used in this research are five years, starting from 2018-2022. Samples were taken using the purposive sampling method. A population of 43 companies listed on the Indonesian Stock Exchange obtained 33 companies as samples with an observation period of five years (2018-2022). Data were analyzed using panel data regression. Based on the results of data analysis, it was concluded that the board of commissioners had no positive and insignificant effect on financial performance and Audit Committee has a positive and significant effect on financial performance.